Exploring determinants of firms' collaboration with specific universities: employee-driven relations and geographical proximity. Issue 8 (3rd August 2017) - Drejer, Ina; Østergaard, Christian Richter
ABSTRACT: Exploring determinants of firms' collaboration with specific universities: employee-driven relations and geographical proximity. Regional Studies . This analysis of the determinants of firms' collaboration on innovation with specific universities assesses both the separate and the overlapping importance of geographical proximity and employee-driven relations for collaboration. It is argued that social, cognitive and functional dimensions of employee-driven relations can help firms to overcome geographical distance. Based on a sample of 2301 innovative firms in Denmark, the study demonstrates that employee-driven relations (measured by employees' and top managers' place of education and scientific discipline) strongly influence the likelihood that firms will collaborate with specific universities. The study confirms the existence of separate and overlapping effects of employee-driven relations and geographical proximity.